THE EFFECT OF GROWTH AND SURVIVAL RATE OF GURAMI (Osphronemus gouramy) FED PHYTASE ENZYM WITH RECIRCULATION SYSTEM - Ikram, Algi Irsanul; Pamukas, Niken Ayu; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research was conducted in October to December 2019 in the Hatchery at Fisheries and Marine Faculty, University of Riau. The aims of this researchwas todetermine the growth and survival rate of Osphronemus gouramy fed phytase enzym with different amounts. Theresearch used a size aquarium 40 x 40 x 40 cm3 with a water height 15 cm for 15 units. The feed used in the form of Phytase Enzym, given with dose of 0,5 g/kg feed, 0,75 g/kg feed, 1 g/kg feed and 1,25 g/kg feed respectively. The method used in this researchwas the experimental method of Completely Randomized Design (CRD) using one factor with 5 treatments and3 replications.The best result is P3feeding with dose 1 g/kg feed can produce absolute growth weight 4,48 gram, absolute growth length 1,67 cm, growth of specific length 2,08%, feed efficiency 25,46% and survival rate 82.22%. Water quality recorded during the research was obtained, temperature 26,3-28,3 0C, pH 7,6-7.9 DO 6,4-6,6 mg/L and Ammonia 0,112-0,128 mg/L.These result of researchof Osphronemus gouramy addedphytase enzym with different amounts gives a significant effect on the growth rate and survival. Keywords: Osphronemus gourami, Phytase Enzym, Growth and survival rate,